29 Engineering CD16-Enhanced Stem Cell–Derived Universal NKT Cells to Potentiate Anti-CD70 Therapy in Renal Cell Carcinoma - Yan-Ruide Li; Yichen Zhu; Yuning Chen; Thomas Yuen; Shelby Yeh (The Oncologist, 2026)
Abstract Background Renal cell carcinoma (RCC) frequently exhibits upregulation of CD70, a tumor-associated antigen implicated in immune evasion and disease progression, making it an attractive therapeutic target. Cusatuzumab, an Fc-enhanced anti-CD70 monoclonal antibody, has demonstrated the ability to mediate antibody-dependent cellular cytotoxicity (ADCC); however, its clinical efficacy is limited by insufficient effector cell engagement, antigen heterogeneity, and adaptive resistance mechanisms within the tumor microenvironment. Methods To overcome these limitations, we developed a universal, off-the-shelf natural killer T (NKT) cell product derived from hematopoietic stem cells (HSCs) through genetic engineering of an invariant T cell receptor (TCR) and a high-affinity, non-cleavable CD16 receptor. These CD16-enhanced HSC-derived NKT (CD16HSC-NKT) cells were generated using a feeder-free differentiation platform, yielding high purity and scalability while preserving canonical NKT cell phenotypes and effector functions. Results Functionally, CD16HSC-NKT cells exhibited potent intrinsic cytotoxicity and multimodal tumor-targeting capabilities. In combination with cusatuzumab, these cells demonstrated robust ADCC against CD70-positive RCC cells both in vitro and in vivo, significantly enhancing tumor cell killing compared to antibody monotherapy. Moreover, CD16HSC-NKT cells displayed improved persistence and functional stability, supporting sustained antitumor activity. Importantly, CD16HSC-NKT cells contributed to remodeling of the tumor microenvironment by selectively depleting immunosuppressive populations, including tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs). Safety assessments indicated a favorable profile, with no evidence of uncontrolled activation or off-target toxicity. Conclusions Collectively, our findings establish CD16HSC-NKT cells as a versatile and scalable cellular platform that synergizes with cusatuzumab to enhance therapeutic efficacy against RCC. This combinatorial strategy represents a promising approach to overcoming current limitations of monoclonal antibody therapy and advancing next-generation immunotherapies for solid tumors.